Sintesis dan aplikasi nanoemulsi betalain kulit buah naga merah (Hylocereus polyrhizus) sebagai pewarna alami pada produk es krim: Synthesis and application of betalain nanoemulsion from red dragon fruit peel (Hylocereus polyrhizus) as natural colorant in ice cream products - Utami, Cahyaning Rini; Ifadah, Qodhrul Izza Irdianis (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Betalains are promising natural colorants, yet their stability often poses challenges. This study employed Deep Eutectic Solvent (DES)–based extraction coupled with nanoemulsion formulation to enhance the stability and performance of betalains from red dragon fruit (Hylocereus polyrhizus) peel for application in ice cream. A completely randomized design with one factor and three replicates was used. Responses measured included betalain content, pH, droplet size, color coordinates (L*, a*, b*), antioxidant activity, and sensory attributes (aroma, color, texture, taste). Increasing extract concentration significantly affected most responses, generally intensifying redness and antioxidant capacity while maintaining desirable physicochemical characteristics. Based on the effectiveness index, formulation F5 (12 mL extract) showed the most favorable overall performance, delivering the highest antioxidant activity, superior physicochemical properties (stable nano-scale droplets, appropriate pH, vivid color), and the greatest sensory acceptance. These results demonstrate that DES-based betalain nanoemulsions are effective natural colorants for ice cream, with F5 recommended as the optimal formulation.